Challenges of managing viper envenomation - Purvesh Agrawal; Nidhi Khandelwal (Wolters Kluwer Medknow Publications, 2022)
The signs and symptoms following snakebite envenomation vary according to the type of snake encountered. Typically, Viperidae (vipers) envenomates with a hemotoxin causing coagulopathy and muscle breakdown, while elapids envenomate with a neurotoxin. However, these are not exclusive; the venom from elapids can have a hemotoxic effect and that of the Viperidae can be neurotoxic. We present a case series of viper envenomation presenting to the emergency department at a secondary care Indian Navy Hospital during 2019-2020. These cases highlight the clinical challenges involved in presentation of viper envenomation.